Meaning-Making Process Related to Temporality During Breast Cancer Traumatic Experience: The Clinical Use of Narrative to Promote a New Continuity of Life - Maria Luisa Martino; Maria Francesca Freda (Europe's Journal of Psychology, 2016)
Previous research has agreed that meaning-making is a key element in the promotion of patients’ well-being during and after a traumatic event such as cancer. In this paper, we focus on an underestimated key element related to the crisis/rupture of this meaning-making process with respect to the time perspective. We consider 40 narratives of breast cancer patients at different times of treatment, undergoing chemotherapy and biological therapy. We collected data through writing technique. We performed an interpretative thematic analysis of the data and highlighted specific ways to signify time during the different treatment phases. Our central aspect “the time of illness, the illness of time” demonstrates that the time consumed by illness has the risk of becoming an illness of time, which transcends the end of the illness and absorbs a patient’s past, present, and future, thus saturating all space for thought and meaning. The study suggests that narrative can become a therapeutic and preventive tool for women with breast cancer in a crisis of temporality, and enable the promotion of new semiotic connections and a specific functional resynchronization with the continuity/discontinuity of life. This is useful during the illness and medical treatment and also after the treatment.